Aktywność fizyczna determinantą zdrowia populacji - Ucieklak-Jeż, Paulina; Bem, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In this paper we verified and analysed the relationship between: (1) cycling (in minutes) and doing another sports, in a typical week, and social determinants of health; (2) moving on foot in public space and social determinants of health; (3) physical activity associated with the performance of work and the social determinants of health; (4) physical activity and health assessment, long-term health problems, diseases and chronic ailments, and athleticism. We constructed three research hypotheses: (H1) residents of densely populated areas (large cities) are physically active; (H2) the longer the time average intensity of physical activity, the healthier the population; (H3) the healthiest group are people physically active. The first hypothesis was positively verified — inhabitants of large cities often spend a lot of time at work, are stressed and need some physical activity. The second hypothesis was confirmed only partially: Chi square = 1692,469; Yul φ = 0,322; Q-Kendalla = 0,297 indicate that there is a statistically significant relationship between the amount of time spent on sports and health. The longer time spent on sport, the better health. The third hypothesis was also confirmed — active physical enjoy better health.
Keywords: physical activity; healthy adults; social determinants of health (SHD)